Factors influencing employee’s quality of life during COVID-19 pandemic - Mulyani, Indah; Rahardjo, Wahyu; Andriani, Inge; Qomariyah, Nurul (Indigenous, 2020)
One result of the COVID-19 pandemic for the wider community, especially employees, is the need to carry out physical distancing in the form of work from home. This phenomenon certainly has consequences on the quality of life felt by employees. The purpose of this study was to determine whether the quality of life of employees who work from home is influenced by variables such as type D personality, anxiety, technology overload, and work-life balance. Participants in this study were 486 employees living in Jakarta Greater Area who worked from home because of the COVID-19 pandemic. Participants were recruited by purposive sampling using online questionnaire. Measurements were made using a measuring tool from each variable using a quantitative approach. Hierarchical regression is used as a data analysis technique. The findings of this research show that all independent variables have an influence on quality of life. However, anxiety has the smallest influence and type D personality has the greatest effect. Meanwhile, like work-life balance, technology overload has positive effect on quality of life. That is, internal and external factors can have different effects on the quality of life felt by employees who work from home due to the COVID-19 pandemic.